Oh, the places you'll go! - Seuss, Dr. (New York : Random House, 1990)
Presents humorous, rhyming advice from Dr. Seuss on how to proceed in life,conquer fear, loneliness and confusion, and take charge of one's own actions.
Elem. School Library Collection.
School Library Journal.
Wilson's Children.
3.2.
3.2
K-3
Keywords: Stories in rhyme; Success -- Fiction; Stories in rhyme; Success -- Fiction